Phagocytosis of platelets enhances endothelial cell survival under serum deprivation - Jiang, Ping (Exp Biol Med (Maywood), 2015)
Platelets are key players in fundamental processes of vascular biology, such as angiogenesis, tissue regeneration, and tumor metastasis. However, the underlying mechanisms remain unclear. In this study, some tumor vascular endothelial cells were positively stained by antiplatelet antibodies. Further investigation revealed that platelets were taken up by endothelial cells in vitro and in vivo. Human umbilical vascular endothelial cells were rendered apoptotic under conditions of serum deprivation. However, endothelial apoptosis was suppressed and cell viability was enhanced when platelets were added to the cultures. Endothelial survival was paralleled by an upregulation of phosphorylated Akt and p70 S6K. In conclusion, this study demonstrated that platelets can be phagocytosed by endothelial cells, and the phagocytosed platelets could suppress endothelial apoptosis and promote cell viability level. The mechanism underlying this process involves the activation of Akt signaling.